The Influence of Transformative Leadership and Adversity Quotient on Teacher Performance - Sedio Mandiri; Dessy Wardiah; Andi Rahman (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the influence of transformational leadership and adversity quotient (AQ) on teacher performance at Sekolah Mandiri Yayasan Jiwa Mandiri Utama Palembang. Employing a quantitative survey method, data were collected via questionnaires, observation, and documentation from all 80 teachers (saturated sample) and analyzed using descriptive statistics, t-tests, F-tests, and coefficient of determination. The results confirm that both transformational leadership and AQ individually have a significant positive effect on teacher performance. Moreover, these factors together exert a significant simultaneous influence, accounting for 35.3% of the variance in performance. The novelty of this research lies in its integration of psychological resilience (AQ) with leadership theory within a private school context in Indonesia, highlighting their combined role in enhancing educator efficacy. A key practical implication is the need for institutional policies that concurrently develop school leaders’ transformational capabilities and foster teachers’ resilience through targeted training and support systems. The study contributes to the field of educational management by demonstrating that teacher performance is optimally strengthened through dual-focused strategies that address both inspirational leadership and individual psychological capacity to overcome challenges.